Human Umbilical Cord-Derived Mesenchymal Stem Cells as a Source of Odontoblasts: a GMP-compliant Approach - Bisaro Brigitte; Mussano Federico; Mattia Silvia; Marmotti Antonio; Forni Marco; Zanini Cristina (Journal of Evolving Stem Cell Research, 2017)
Stem cell-based regenerative therapy can be considered an innovative approach for curing dental caries. Pulp stem cells from human exfoliated deciduous teeth (SHEDs) represent a source of committed cells for generating odontoblasts in vitro; however, SHEDs are not easy to obtain and are limited in quantity. Umbilical cord-derived mesenchymal stem cells (UC-MSCs) are considered to be adult stem cells that can be easily obtained in large numbers. Here, SHEDs and UC-MSCs were conditioned in custom-made serum-free culture media in order to induce differentiation towards odontoblasts. SHEDs and UC-MSCs were expanded in vitro and differentiated into odontoblasts for 21 days using a medium containing transforming growth factor-β (TGF-b3), hepatocyte growth factor (HGF) and growth differentiation factor 5 (GDF5). The ability to induce odontoblast differentiation with a straightforward clinical protocol in compliance with good manufactoring practice (GMP), which avoids animal reagents, and uses unrelated stem cells of unrestricted availability, may be a first step towards a new innovative approach for dentin regeneration.
Keywords: Stem cells